The Relationships of Fibrinogen and C-Reactive Protein With Gait Performance: A 20-Year Longitudinal Study - Heumann, Zohar; Youssim, Iaroslav; Kizony, Rachel; Friedlander, Yechiel; Shochat, Tamar; Weiss, Ram; Hochner, Hagit; Agmon, Maayan (Frontiers in Aging Neuroscience, 2022)
Background: Gait speed, a central marker of aging, has been linked to various health outcomes, such as cognitive and physical functions in middle-aged adults. Although long-term systemic low-grade inflammation is considered a mechanism underlying a variety of aging-related risk factors, the longitudinal associations between inflammation markers and gait speed are yet to be fully investigated. Objective: To explore the associations of CRP and fibrinogen levels, measured two decades ago, with gait speed among community dwelling adults, considering the contribution of cardio-metabolic factors and cognition. Methods: Study participants took part in two phases of the of the “Kibbutzim Family Study” (i.e., Phase II, 1999-2000 and Phase III, 2017-2019). Blood samples collected in Phase II (baseline) were used to determine level of inflammatory markers. Gait speed was assessed under single-task (ST) and dual-task (DT) conditions in Phase III. Demographic, anthropometric and clinical data were collected in both phases. Linear regression models were used to assess the adjusted associations of inflammation and gait speed. Results: 373 individuals aged 34-99 (mean 64±13 years) in Phase III were included in the study. Gait speed under ST was negatively associated with baseline levels of fibrinogen (b=-0.053, p=0.007) and CRP (-0.043, p=0.010), after adjusting for baseline and concurrent cardiometabolic risk factors. Accounting for executive functions, associations of fibrinogen with gait under ST were somewhat attenuated, yet associations remained statistically significant (p<0.05). Associations with CRP were attenuated to the null. In contrast, there were no associations between inflammation markers and gait under DT. Conclusions: Our findings demonstrate that in a sample including also younger to older adults, higher systemic inflammatory activity was linked with gait 20 years later, beyond age and cardiometabolic health, and to a certain extent, beyond executive functions. Thus, systemic inflammation may serve as an early marker to identify individuals at risk for gait decline.